Large-scale whole-exome sequencing association studies identify rare functional variants influencing serum urate levels - Adrienne Tin (Nature Portfolio, 2018)
Elevated serum urate levels are a risk factor for gout. Here, Tin et al. perform whole-exome sequencing in 19,517 individuals and detect low-frequency genetic variants in urate transporter genes, SLC22A12 and SLC2A9, associated with serum urate levels and confirm their damaging nature in vitro and in silico.